Stuck in the Tunnel: Is Globalization Muddling the Middle Class? - Nancy Birdsall; Carol Graham; Stefano Pettinato (Luxembourg Income Study (LIS), 2000)
Our objective in this paper is to assess how middle-income groups are faring with the global turn to the market. We suggest some simple measures of the middle-the size and income shares of households around the median (75/125%)-and their income status relative to wealthier counterparts. Our results point to genuine distributional stress for middle-income households, as well as public perceptions of such stress. They also suggest the need for new measures to capture distributional trends that are masked by aggregate measures. We posit that the fate of those in the middle merits new attention, as their political support and economic participation are critical to sustainable, market-oriented growth and poverty reduction in the long-term.
Keywords: 330; Einkommensverteilung; Globalisierung; Mittelschicht; Sozialer Wandel; Welt